Crescentiella, a new name for "Tubiphytes" morronensis Crescenti, 1969 : an enigmatic Jurassic - Cretaceous microfossil - Senowbari-Daryan, Baba (Array, 2008)
Summary: Several organisms or interaction of organisms have been described over a long time interval from the Late Palaeozoic to Cretaceous as Tubiphytes, with the type species being T. obscurus MASLOV, 1956. Palaeozoic Tubiphytes were revised by SENOWBARI-DARYAN & FLÜGEL (1993). Triassic representatives still need to be revised. For Jurassic (extremely abundant in upper Jurassic) and Cretaceous organisms, known as “Tubiphytes” morronensis CRESCENTI, 1969, we propose here the genus name Crescentiella. Differences between Crescentiella nov. gen. and Tubiphytes MASLOV are discussed. The systematic position of Crescentiella as a foraminifera, interaction of foraminifera and cyanophyceans or as a special kind of oncolite is discussed. It is interpreted as symbiosis or encrustation between cyanobacteria and a nubecularid foraminifera, uncertain tube or rarely, other biogenic components. Comments on similar associations, e.g. the genus Labes ELIASOVA, are provided